Skin Cancer Detection Using Deep Learning and Artificial Intelligence - Abdelaziz, Ahmed (2022)
Abdelaziz, A., & Mahmoud, A. N. (2022). Skin Cancer Detection Using Deep Learning and Artificial Intelligence: Incorporated model of deep features fusion. Fusion: Practice and Applications, 8(2), 8-15. https://doi.org/10.54216/FPA.080201 © 2022, American Scientific Publishing Group (ASPG). All rights reserved.